2005
DOI: 10.1007/s10038-005-0279-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase (G6PD) mutations in Cambodia: G6PD Viangchan (871G>A) is the most common variant in the Cambodian population

Abstract: We conducted a survey of malaria diagnoses and glucose-6-phosphate dehydrogenase (G6PD) testing in remote areas of Cambodia. Blood specimens from 670 people were collected by the finger-prick method. Of these people, 24.9% were found to have malaria, and 7.0% of people were G6PD deficient. In the Khmer, the largest ethnical population in Cambodia, the G6PD deficiency rate of males was 12.6% (25/199) whereas the rates in the minorities of the Tum Pun and the Cha Ray were 1.1% (1/93) and 3.2% (2/63), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 19 publications
8
37
2
Order By: Relevance
“…This finding confirms the results of previous reports that G6PD Mahidol is the predominant mutation in Burmese and Mon people in Myanmar (Iwai et al 2001;Matsuoka et al 2004). Our findings in Mon are in sharp contrast with two previous studies of Cambodians in which G6PD Viangchan was found to be the most common G6PD deficient mutation: 28 of 34 (82.4%) in one study (Louicharoen and Nuchprayoon 2005) and 46 of 47 (96.5%) in the other (Matsuoka et al 2005) and G6PD Mahidol was not present in any of the G6PD-deficient Cambodians.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding confirms the results of previous reports that G6PD Mahidol is the predominant mutation in Burmese and Mon people in Myanmar (Iwai et al 2001;Matsuoka et al 2004). Our findings in Mon are in sharp contrast with two previous studies of Cambodians in which G6PD Viangchan was found to be the most common G6PD deficient mutation: 28 of 34 (82.4%) in one study (Louicharoen and Nuchprayoon 2005) and 46 of 47 (96.5%) in the other (Matsuoka et al 2005) and G6PD Mahidol was not present in any of the G6PD-deficient Cambodians.…”
Section: Discussionsupporting
confidence: 86%
“…G6PD mutations in Southeast Asians are specific to certain ethnic groups. G6PD Viangchan (871G [ A; Val291Met) is the most common mutation among Thais (Nuchprayoon et al 2002), Laotians (Iwai et al 2001), and Cambodians (Louicharoen et al 2005;Matsuoka et al 2005), whereas G6PD Mahidol (487G [ A; Gly163Ser) is the most common mutation among Burmese in Myanmar (Matsuoka et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of G6PD deficiency in males in Thailand's neighboring countries where malaria is endemic was 11.0% in Myanmar (Matsuoka et al 2004), 12.6% in Cambodia (Matsuoka et al 2005), and 2.7-7.2% in Malaysia (Ainoon et al 2003). Although no malarial infection was observed, the prevalence of male G6PD deficiency in Southern Phuket (9.8%) was comparable to these latter values.…”
Section: Discussionsupporting
confidence: 51%
“…G6PD Gaohe (95A>G) was found exclusively in Chinese (Iwai et al 2001), whereas G6PD Mahidol (487G>A) and G6PD Viangchan (871G>A) was the most common variant in Myanmer (91.3%) (Matsuoka et al 2004), and in Laotian (100%) (Hsia et al 1993) and Cambodia (97.9%) (Matsuoka et al 2005), respectively. The Moken have been recorded in the literature as having had contact with traders from the continental countries such as Myanmar and China (Ivanoff 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, almost all of G6PD deficient cases detected in Laos (Iwai et al 2001) and Cambodia (Louicharoen and Nuchprayoon 2005;Matsuoka et al 2005) are G6PD Viangchan. This variant is also the most common in Thais (54%, Nuchprayoon et al 2002;31.3%, Laosombat et al 2005) and Malaysian Malays (37.2%, Ainoon et al 2003), suggesting that this is a common ancestral origin of continental Southeast Asian populations.…”
Section: Introductionmentioning
confidence: 99%